Wage Posting and Business Cycles - Moscarini, Giuseppe; Postel-Vinay, Fabien (American Economic Review, 2016)
The canonical model of job search and wage posting (Burdett and Mortensen, 1998) establishes a natural connection between the average wage growth in the economy and the pace of Employer-to-Employer (EE) transitions, predicting wage growth to be positively related to the pace of EE reallocation for all workers, but especially for stayers. We verify this empirically both with aggregate time series and with longitudinal micro data from the Survey of Income and Program Participation (SIPP). We argue that monetary authorities concerned with inflationary wage pressure should pay more attention directly to EE reallocation and less to the unemployment rate.